Nortriptyline for neuropathic pain in adults - Derry, Sheena; Wiffen, Philip J; Aldington, Dominic; Moore, R Andrew (Cochrane database of systematic reviews, 2015)
Antidepressants are widely used to treat chronic neuropathic pain (pain due to nerve damage), usually in doses below those at which they exert antidepressant effects. An earlier review that included all antidepressants for neuropathic pain is being replaced by new reviews of individual drugs examining individual neuropathic pain conditions.Nortriptyline is a tricyclic antidepressant that is occasionally used for treating neuropathic pain, and is recommended in European, UK, and USA guidelines. To assess the analgesic efficacy and associated adverse events of nortriptyline for chronic neuropathic pain in adults. We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, and EMBASE from inception to 7 January 2015, and the reference lists of retrieved papers and other reviews. We also searched two clinical trials databases for ongoing or unpublished studies. We included randomised, double-blind studies of at least two weeks' duration comparing nortriptyline with placebo or another active treatment in chronic neuropathic pain. Participants were adults aged 18 years and over. We included only full journal publication articles and clinical trial summaries. Two review authors independently extracted efficacy and adverse event data, and examined issues of study quality. We considered the evidence using three tiers. First tier evidence derived from data meeting current best standards and subject to minimal risk of bias (outcome equivalent to substantial pain intensity reduction, intention-to-treat analysis without imputation for dropouts; at least 200 participants in the comparison, 8 to 12 weeks' duration, parallel design); second tier evidence from data that failed to meet one or more of these criteria and were considered at some risk of bias but with adequate numbers in the comparison; and third tier evidence from data involving small numbers of participants that was considered very likely to be biased or used outcomes of limited clinical utility, or both.We planned to calculate risk ratio (RR) and numbers needed to treat for an additional beneficial outcome (NNT) and harmful outcome (NNH) using standard methods expected by The Cochrane Collaboration. We included six studies treating 310 participants (mean or median age 49 to 64 years) with various neuropathic pain conditions. Five studies used a cross-over design, and one used a parallel-group design; 272 participants were randomised to treatment with nortriptyline, 145 to placebo, 94 to gabapentin, 56 to gabapentin plus nortriptyline, 55 to morphine, 55 to morphine plus nortriptyline, 39 to chlorimipramine, and 33 to amitriptyline. Treatment periods lasted from three to eight weeks. All studies had one or more sources of potential major bias.No study provided first or second tier evidence for any outcome. Only one study reported our primary outcome of people with at least 50% reduction in pain. There was no indication that either nortriptyline or gabapentin was more effective in postherpetic neuralgia (very low quality evidence). Two studies reported the number of people with at least moderate pain relief, and one reported the number who were satisfied with their pain relief and had tolerable adverse effects. We considered these outcomes to be equivalent to our other primary outcome of Patient Global Impression of Change (PGIC) much or very much improved.We could not pool data, but third tier evidence in individual studies indicated similar efficacy to other active interventions (gabapentin, morphine, chlorimipramine, and amitriptyline), and to placebo in the conditions studied (very low quality evidence). Adverse event reporting was inconsistent and fragmented. More participants reported adverse events with nortriptyline than with placebo, similar numbers with nortriptyline and other antidepressants (amitriptyline and chlorimipramine) and gabapentin, and slightly more with morphine (very low quality evidence). No study reported any serious adverse events or deaths. We found little evidence to support the use of nortriptyline to treat the neuropathic pain conditions included in this review. There were no studies in the treatment of trigeminal neuralgia. The studies were methodologically flawed, largely due to small size, and potentially subject to major bias. The results of this review do not support the use of nortriptyline as a first line treatment. Effective medicines with much greater supportive evidence are available, such as duloxetine and pregabalin.